PERKEBUNAN SEBAGAI POTENSI UTAMA EKONOMI MASYARAKAT DESA WAIMI KECAMATAN LEMBUR - Vani E. Maniyeni; Welmince Onbila; Petrus Mau Telu Dony (Adiba Aisha Amira, 2026)
This study aims to describe the potential of plantations as the main supporter of the economy of the Waimi village community, Lembur sub-district. The study uses a qualitative method with an interview techninque with the Waimi village head as the main data source. The results of the study indicate that the most superior potential in the village, with the main commodities being candlenut, areca nyt and betel. Candlenut functions as an alternative source of income in economic commodities, areca nut and betel area plants that have a very important role fot the community because they are used as one of the commodities that help the commodity to meet their living needs. Plantaton activities are carried out from generation to generation and are an important part of community life. Based on these findings, plantions are a sector that drives the economy of the Waimi village community.